(untitled) (Bangladesh Medical Journal, 2014)
Wolff-Parkinson-White syndrome is a disorder characterized by presence of an accessory pathway which predisposes patients to tachyarrhythmias and sudden death. Among patients with WPW syndrome, atrioventricular reentrant tachycardia (AVRT) is the most common arrhythmia, accounting for 95% of re-entrant tachycardias. It has been estimated that one-third of patients with WPW syndrome have atrial fibrillation (AF). AF is a potentially life-threatening arrhythmia. If an accessory pathway has a short anterograde refractory period, then rapid repetitive conduction to the ventricles during AF can result in a rapid ventricular response with subsequent degeneration to ventricular fibrillation (VF). The study population included a total of 255 patients in whom 175 (68.62%) were men and 80 (31.38%) were women. Demographic data and clinical characteristics are depicted in Table 1. Left and right WPW syndrome were existing in 70.59% and 29.41% of patients respectively. Documented narrow QRS SVT was present in 96.86%, broad QRS SVT was in 2.75% and AF was in 3.14% of patients. Antiarrhythmic drugs most frequently used were Digitalis, Metoprolol, Sotalol, Amiodarone and Verapamil DOI: http://dx.doi.org/10.3329/bmj.v41i2.18809 Bangladesh Medical Journal 2012 Vol. 41 No. 2: 50-53